유아 자아탄력성 척도 개발 및 타당화 연구 - 이수기(Suki Lee) (한국콘텐츠학회 논문지, 17(2), 2017)
The purpose of this study is to develop a children's ego-resilience measurement scale and to examine the reliability and validity of the developed scale. Subjects consisted of 289 children of age 3 to 5 attending kindergarten and daycare centers located in Gwangju city and Chonnam province. Factor analysis, correlation analysis and reliability analysis were conducted using SPSS 18.0 and Amos 18.0 programs. The children's ego resilience scale consists of 26 items of 5 factors(attention concentration, emotion control, self efficacy, empathy, peer relationship) after the exploratory factor analysis. The confirmatory factor analysis revealed that RMSEA is .059, NNFI is .901 and CFI is .913. Pearson's product moment correlation coefficient were acceptable with this study's scale and KPRC. Chronbach ${α}$ were also acceptable. Thus, the developed children's ego resilience measurement scale is reliable and valid. 본 연구의 목적은 유아의 자아탄력성을 측정할 수 있는 척도를 개발하여 타당도와 신뢰도를 검증하는 것이다. 연구대상은 광주광역시와 전남지역에 소재한 유아교육기관에 재원하고 있는 만3, 4, 5세 유아 289명이었다. 수집된 자료는 SPSS 18.0, AMOS 18.0 프로그램을 사용하여 요인분석과 신뢰도 분석을 하였다. 탐색적 요인분석 결과 '주의집중', '정서조절', '자기효능감', '공감', '또래관계'의 5개 요인의 26문항이 구성되었다. 확인적 요인분석 결과 모델 적합도 지수는 RMSEA=.059, NNFI=.901와 CFI=.913로 나타났고, 공인타당도 검증을 위해 KPRC의 자아탄력성 척도와 상관관계를 확인한 결과 두 척도 간에는 높은 상관을 보이는 것으로 나타났다. 또한 내적일관성 지수인 Chronbach ${α}$를 분석한 결과 신뢰도도 양호한 것으로 나타났다. 따라서 본 연구에서 개발된 척도는 유아의 자아탄력성을 측정하기 위한 척도로서 신뢰도와 타당도가 적합한 것으로 나타났다.